Non-Invasive Imaging of Vascular Inflammation - Ammirati, Enrico; Moroni, Francesco; Pedrotti, Patrizia; Scotti, Isabella; Magnoni, Marco; Bozzolo, Enrica P.; Rimoldi, Ornella E.; Camici, Paolo G. (Frontiers in Immunology, 2014)
In large-vessel vasculitides, inflammatory infiltrates may cause thickening of the involved arterial vessel wall leading to progressive stenosis and occlusion. Dilatation, aneurysm formation, and thrombosis may also ensue. Activated macrophages and T lymphocytes are fundamental elements in vascular inflammation. The amount and density of the inflammatory infiltrate is directly linked to local disease activity. Additionally, patients with autoimmune disorders have an increased cardiovascular risk compared with age-matched healthy individuals as a consequence of accelerated atherosclerosis. Molecular imaging techniques targeting activated macrophages, neovascularization or increased cellular metabolic activity can represent effective means of noninvasive detection of vascular inflammation. In the present review novel noninvasive imaging tools, that have been successfully tested in humans, will be presented. These include contrast enhanced ultrasonography, which allows detection of neovessels within the wall of inflamed arteries; contrast enhanced cardiovascular magnetic resonance that can detect increased thickness of the arterial wall, usually associated with edema, or mural enhancement using T2 and post-contrast T1-weighted sequences respectively; and positron emission tomography associated with radio-tracers such as [18F]-fluorodeoxyglucose and the new [11C]-PK11195 in combination with computed tomography angiography to detect activated macrophages within the vessel wall. Imaging techniques are useful in the diagnostic work-up of large- and medium-vessel vasculitides, to monitor disease activity and the response to treatments. Finally, molecular imaging targets can provide new clues about the pathogenesis and evolution of immune-mediated disorders involving arterial vessels.